Internacionalizac??o como vantagem competitiva: estudo de caso da empresa brasileira de software Datasul - Ortega, Andr??a Aparecida Cassan (2009)
The objective of this thesis is to analyze the factors that contributed to the internationalization of the Brazilian company in the area of software Datasul. Globalisation and the consequent interaction of markets made the spatial location of the software industry an important factor for competitiveness. Many companies in developing countries do not consider themselves able to explore other markets due to technological gap between global companies and their local standards. This thesis seeks to show that business innovation is a major factor responsible for the success of companies of this company winning the world market. The internationalization process of firms is discussed according to the traditional behavioral model developed by the School of Uppsala. This thesis is based on case study of the Brazilian Software DATASUL, dedicated to developing integrated management systems, better known as Enterprise Resource Planning (ERP). The case shows that innovation and internationalization are factors that contribute to the company's competitiveness in domestic and global. This dissertation was written before the merger between the group Datasul Totvs